Overview of the NASA Solar Irradiance Science Team (SIST) Program Special Section - Matthew T. DeLand; Greg Kopp; David B. Considine (Earth and Space Science, 2019)
Abstract Solar irradiance represents the dominant energy source heating the Earth's atmosphere and climate. Both total solar irradiance and spectral solar irradiance vary over the 11‐year solar cycle. Characterizing these variations with sufficient accuracy for climate studies over multidecadal timescales requires a combination of multiple observational data sets, solar activity proxies, and irradiance models. NASA established the Solar Irradiance Science Team (SIST) program in 2015 to pursue this goal using a range of technical approaches. This paper summarizes those investigations, whose results are reported in separate papers in a special section of this journal.